Systematic Literature Review on Guidance and Counseling Using Cognitive Behavioral Therapy for Online Game Addiction - Lestari, Puput; Damayanti, Rika; Masya, Hardiyansyah; Thahir, Andi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study explores the use of Cognitive Behavior Therapy (CBT) in guidance and counseling services to address online game addiction. The researchers employed the SLR (systematic literature review) approach compiled using the PRISMA Method and scanned with Vosviewer software. The number of participants varied, with the largest number being 7129. Other numbers of participants included 2-20 subjects, 30-100 subjects, and two subjects with the least number of participants. The findings highlight that CBT, often combined with supplementary techniques, effectively reduces online game addiction by adapting strategies to individual needs. Family involvement plays a crucial role, serving as both a source of support and a potential contributing factor. Counselors frequently appoint a family member to assist in managing the counselee, and in severe cases, CBT is complemented by other therapeutic approaches or medications to address related psychological issues. Alternative therapies, such as Behavior Change Techniques (BCT), Behavior Change Strategies (BCS), and Acceptance Commitment Therapy (ACT), further enhance the treatment's efficacy. This study contributes to the field by emphasizing the adaptability and impact of CBT in addressing online game addiction while calling for future research on integrating CBT with other interventions and preventive measures across diverse cultural contexts.